Pulsed Laser Ranging Techniques Based on Digital Signal Processing Methods for Proximity Fuze - Nguyen, Hoang-Linh; Nguyen, Dinh-Dung; Vuong, Anh-Trung; Tran, Hong-Son (European Journal of Applied Sciences, 2022)
Laser fuze systems play an emerging part in military technology bases nowadays. In the paper, a solution is developed to improve the accuracy of the laser rangefinder system in laser fuze without changing the hardware design of the digital signal processor. The proposed algorithm will combine real-time pulse processing techniques used in target range measurement. The new algorithm interpolates returned data using a relatively low sampling rate to a higher one. It applies a cross-correlation technique using high-resolution reference waveform models to restore the position of the super-sampled start and return pulses. Based on the Monte Carlo method and simulating the waveform in the noise environments, 100 trials were judged on the standard deviation of the range estimations. With the presentation of detection performance comparison results between range estimation algorithms of laser fuzes, this paper can provide guidance and references for the application in the proximity fuze.